LANDSCAPE AND FLORAL EMBLEMS AS A KEY TO COMPREHENDING ARTISTIC SECRETS OF THE POSTMODERN NOVELS “THE MAGUS” BY JOHN FOWLES AND “RARE EARTHS” BY VASILY AKSYONOV - Vitalievna Kochergina, Valeria; Vladimirovna Krivchenkova, Irina (Revista Inclusiones, 2019)
The novels “The Magus” by John Fowles and “Rare Earths” by Vasily Aksyonov are rich with cultural allusions. In both novels, belonging to different time periods and national cultures, floral emblems are present. In “The Magus”, Fowles uses floral codes as beacons –clues to secrets and hidden meanings of the novel. Aksyonov, in turn, uses floral symbols not only at the narrative level but also in an attempt to identify the main character. Decoding floral emblems hidden in the novels allows the reader to identify the main characters and find answers to many other questions concerning the meaning of the title, as well as the aim and significance of the novels for the authors themselves.